A Two‐Step Synthesis of 2‐Spiropiperidines. Issue 39 (22nd June 2017) - Griggs, Samuel D.; Thompson, Nathan; Tape, Daniel T.; Fabre, Marie; Clarke, Paul A.
Abstract: A general two‐step synthesis of 2‐spiropiperidines has been developed. δ‐Amino‐β‐ketoesters can be reacted with cyclic ketones to generate 2‐spiropiperidines in good to excellent yields. The 2‐spiropiperidines formed occupy an under‐explored region of 3D‐chemical space and are novel scaffolds for use in drug discovery programs. These 2‐spiropiperidines can be further functionalised to generate small highly sp 3 ‐rich structures, which exhibit an excellent likeness to lead‐molecules in drug discovery. Abstract : Spiro‐tastic ! 2‐Spiropiperidines have been readily synthesised in good to excellent yields by means of a two‐step procedure. These molecules constitute novel 3D‐scaffolds for use in drug discovery programs, occupying an under‐populated region of chemical space. The 2‐spiropiperidines formed can be readily modified into lead‐like molecules.